Epistemologi Etika Ekologis dalam Tafsir Al-Mishbah karya Muhammad Quraish Shihab: Epistemology of Ecological Ethics in Tafsir Al-Mishbah by Muhammad Quraish Shihab - Abdullah Kafabihi; Made Saihu; Nurbaiti Nurbaiti (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2026)
The global ecological crisis requires a theological response that goes beyond moral appeals and is rooted in humanity's spiritual awareness within the divine cosmic order. This study aims to formulate the epistemological framework of Quranic ecological ethics by analyzing the principle of tawhid as the ontological foundation of the unity of creation, the dual subjectivity of humans as khalifah and abd as the anthropological basis, and the concept of amanah as humanity's cosmic responsibility in managing the earth. This framework is further elaborated through three ecological ethical principles governing the human-nature relationship: taskhir, the responsible utilization of nature; mizan, the principle of cosmic balance; and the prohibition of fasad, an indicator of ecological destruction resulting from moral deviation. This research employs a thematic Quranic interpretation (tafsir mawdui) based on library research, with Tafsir Al-Mishbah by Muhammad Quraish Shihab as the primary reference. The findings show that these principles form a transcendent, holistic, and applicable system of Quranic ecological ethics. This study contributes to Ulumul Quran by proposing a Quranic ecological ethical paradigm as a theological foundation for environmental sustainability.